2015
DOI: 10.2139/ssrn.2668891
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Veneration: Public Support for a New Constitutional Convention

Abstract: At the conclusion of Our Undemocratic Constitution, Sanford Levinson asks the American people to call a new constitutional convention. Levinson's critics dismissed this call as fanciful, not least because of the assumption that the populace unthinkingly venerates the Constitution too much to countenance the idea of a convention. We challenge the conventional wisdom on conventions by analyzing a 2011 Time magazine poll indicating one in three Americans would support such a call. While constitutional support rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(34 citation statements)
references
References 75 publications
0
34
0
Order By: Relevance
“…Scholars have also found that other factors figure prominently in generating constitutional support. Blake and Levinson (2016) find that one's legal consciousness (e.g. their preferred mode of constitutional interpretation) shapes constitutional attitudes and support; in examining support for a federal constitutional convention, the authors find that convention support is linked to how one evaluates her legal standing relative the constitutional status quo bias.…”
Section: Existing Research and Shortcomingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Scholars have also found that other factors figure prominently in generating constitutional support. Blake and Levinson (2016) find that one's legal consciousness (e.g. their preferred mode of constitutional interpretation) shapes constitutional attitudes and support; in examining support for a federal constitutional convention, the authors find that convention support is linked to how one evaluates her legal standing relative the constitutional status quo bias.…”
Section: Existing Research and Shortcomingsmentioning
confidence: 99%
“…However, they do not address wholescale constitutional replacement. Blake and Levinson (2016) are closer to the mark examining federal constitutional convention support, but their study is geared more towards constitutional interpretation rather than determining if a person's constitutional loyalty was affected.…”
Section: Existing Research and Shortcomingsmentioning
confidence: 99%
See 3 more Smart Citations